AUTOMATED INVENTORY MANAGEMENT - AMRI, Rami Zayed (2022)
Disclosed are methods, systems, and computer-readable medium to perform operations including: calculating a current weight of a bought-in material over a current period; calculating a current weighted unit price of the bought in material; calculating a historical weighted average price of the bought-in material during a historical period; calculating a difference between the current weighted unit price and the historical weighted average price; calculating a material price percentage change by dividing the difference by the historical weighted average price; multiplying the material price percentage change by the current weight to obtain a weighted average percentage change for the bought-in material; and performing one or more actions in connection with the weighted average percentage change. Des procédés, des systèmes et un support lisible par ordinateur sont divulgués pour effectuer des opérations consistant : à calculer un poids actuel d'un matériau sous-traité pendant une période actuelle ; à calculer un prix unitaire pondéré actuel du matériau sous-traité ; à calculer un prix moyen pondéré historique du matériau sous-traité pendant une période historique ; à calculer une différence entre le prix unitaire pondéré actuel et le prix moyen pondéré historique ; à calculer un changement de pourcentage de prix de matériau en divisant la différence par le prix moyen pondéré historique ; à multiplier le changement de pourcentage de prix du matériau par le poids actuel pour obtenir un changement de pourcentage moyen pondéré pour le matériau sous-traité ; à effectuer une ou plusieurs actions en liaison avec le changement de pourcentage moyen pondéré.